PACARAN SEHAT, GENERASI KUAT: STRATEGI, HAMBATAN, DAN PELUANG BAGI GENERASI MILENIAL - Rotua Setiani Sinaga; Sriwati Sihombing; Stanley Sitorus; Tivo Juan Simanjuntak; Yosafat Timothy Limbong; Damayanti Nababan (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
This article is a research through Christian Religious Education counseling for adults which discusses "Healthy Dating." Nowadays, when it comes to dating, adults no longer consider this a difficult thing, considering themselves to have sufficient ability to determine the actions they take in dating, so it is not uncommon to find adults whose relationships are broken and do not match the teachings of their religion. Dating is no longer a taboo subject for adults, therefore it is necessary to teach and guide these adults for such assumptions. Christian Religious Education aims to guide, foster, and express guilt for all actions that are contrary to God's will in order to qualify someone before God Himself. Unhealthy dating is a dating phenomenon that deviates from the essence of courtship itself. In maintaining a healthy relationship, there are several tips, including praying to God, organizing, need for action, fear God and have a good relationship with God, and personality.